TRANSFORMASI STRATEGI PEMASARAN DIGITAL DALAM PEMASARAN PERUMAHAN DENGAN METODE PESAN BANGUN DI KOTA KENDARI: TRANSFORMASI STRATEGI PEMASARAN DIGITAL. - Eko Marsolisdiono; Silfani Arfita Utami Arfah; Aksan (LPPM AMBKENDARI, 2026)
This study aims to analyze the transformation of digital marketing strategies in housing marketing using the Pesan Bangun method in Kendari City. Rapid population growth and the shift in consumer behavior toward the digital era require housing developers to adapt more innovative marketing communication strategies. The research method used was descriptive qualitative, with data collection techniques through field observation, documentation, and in-depth interviews with developers and resident informants at BTN Griya Permata Hijau and BTN Anduonohu ​​Permai. The results show that the transformation of digital housing marketing strategies through social media ecosystems such as Facebook, Instagram, and TikTok, as well as the use of WhatsApp Business, has changed the paradigm of conventional property marketing in Kendari City. Digital platforms serve not only as promotional tools but also as crucial instruments in building transparency and trust among tech-savvy consumers. Through 3D content visualization and daily vlogs of construction progress, developers have successfully addressed the emotional needs of young families for customizable housing from the planning stage. Field findings confirm that virtual consumer involvement in the design process provides significant added value compared to ready-to-move-in units (ready-stock). The study's conclusions emphasize that integrating sophisticated digital marketing strategies with the flexibility of the Pesan Bangun method is key to winning market loyalty. This synergy simplifies administrative processes through digital document verification and accelerates sales conversion through BTN's transparent mortgage financing scheme. The Segmenting, Targeting, and Positioning (STP) strategy, enhanced by digital data analytics, has proven to be able to create a sustainable competitive advantage for developers amidst the intense competition in the local housing industry.